First Tonic-Clonic Seizure: Treatment and Prognosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The outcome of immediate treatment (carbamazepine, phenytoin, phenobarbital, or sodium valproate) or delayed treatment after a second seizure, in two groups of patients followed for a minimum of 3 years, was evaluated in a multicenter, randomized, open trial reported by the "FIRST Group" from Segrate, Italy.